Methotrexate Induced Severe Bone Marrow Suppression with Low Dose - Adhikari, Sushil; Tiwari, Nishan; Sharma, Swapnil; Pokharel, Abinash (Journal of College of Medical Sciences-Nepal, 2023)
Methotrexate is a first line drug for Rheumatoid arthritis. It is also being used for various autoimmune diseases and in cancer as a chemotherapeutic agent for decades. It works as a folic acid antagonist in cancer. However it works by inhibiting enzyme AICAR and thereby raising intracellular adenosine in autoimmune diseases. Adverse effects can range from mild gastrointestinal disturbance to severe life-threatening pancytopenia, hepatotoxicity, infection and lymphoproliferative disorders requiring hospital admission. Before initiating this drug physician should be aware of its potential harmful effects especially in old and co-morbid patients. Complete blood count, Liver and kidney function test and serology are essential before considering this drug.